2003
DOI: 10.1097/01.shk.0000091205.08003.fd
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Administration of ??-Melanocyte-Stimulating Hormone or Combined Therapy with Bay 11-7085 Protects Against Gut Ischemia???Reperfusion Injury

Abstract: Gut ischemia-reperfusion (I/R) injury is a serious complication of shock. Previously we demonstrated that the administration of alpha-melanocyte-stimulating hormone (MSH) immediately before mesenteric I/R protected against postischemic gut injury. In this report, we tested the therapeutic efficacy of alpha-MSH on gut I/R (60 min ischemia, 6 h reperfusion) injury when given at different time points of reperfusion. Rats underwent sham surgery or were treated with saline or with alpha-MSH that was given 1, 2, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…These results further strengthen the role of αMSH as a potent antiinflammatory molecule [5,14] which exerts its effect by inhibition of the NF-κB transcription factor. Indeed, NF-κB inhibition was found to be central in the protective effect of α-MSH against oxidative stress in IEC-6 rat intestinal cells [40] and against ischemia/reperfusion induced intestinal injury in rats [19,20]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results further strengthen the role of αMSH as a potent antiinflammatory molecule [5,14] which exerts its effect by inhibition of the NF-κB transcription factor. Indeed, NF-κB inhibition was found to be central in the protective effect of α-MSH against oxidative stress in IEC-6 rat intestinal cells [40] and against ischemia/reperfusion induced intestinal injury in rats [19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…In a rat model of chemically induced acute and chronic colitis α-MSH reduced pathological weight loss, fecal blood, TNF-α and nitric oxide production in colon tissue [17] and macroscopic colitis lesions [18]. Protective effect of α-MSH was also described in rat models of intestinal ischemia/reperfusion, where NF-κB induced inflammation has a central role in the pathomechanism [19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…These distinct phases coincided with NF-B activation through different IB␣ phosphorylation pathways-an early phase representing Ser-32, Ser-36 phosphorylation of IB␣ (11), which was inhibited by BAY 11-7085, and a later phase corresponding to tyrosine phosphorylation of IB␣, which was inhibited by the tridecapeptide ␣-melanocyte-stimulating hormone (␣-MSH) (8)(9)(10). In the aggregate, our data suggested that NF-B activation by the classical pathway of serine phosphorylation of IB␣ plays an important role in the injury response of the ileum during the early reperfusion period following mesenteric ischemia.…”
Section: Introductionmentioning
confidence: 98%
“…In previous work, we showed that mesenteric I/R results in a biphasic activation pattern of NF-B DNA-binding activity in the postischemic rat ileum during reperfusion (8)(9)(10). These distinct phases coincided with NF-B activation through different IB␣ phosphorylation pathways-an early phase representing Ser-32, Ser-36 phosphorylation of IB␣ (11), which was inhibited by BAY 11-7085, and a later phase corresponding to tyrosine phosphorylation of IB␣, which was inhibited by the tridecapeptide ␣-melanocyte-stimulating hormone (␣-MSH) (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The ischemia is consequent to the nonphysiologic perfusion during CPB, a potent stimulus for the release of endogenous splanchnic vasoconstrictors such as angiotensin II (4), and the activation of complement system (5) and proinflammatory cytokines (6,7), which also activate platelets and leukocytes (8,9) to form cellular aggregates capable of occluding vessels within the microcirculation. Free radical production and related cytotoxicity are pivotal as intermediates of these factors in various types of mesenteric ischemia and reperfusion injury (9,10).…”
Section: Introductionmentioning
confidence: 99%